2017
DOI: 10.1136/bmj.j273
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care delivered by general internists in US hospitals who graduated from foreign versus US medical schools: observational study

Abstract: Objective To determine whether patient outcomes differ between general internists who graduated from a medical school outside the United States and those who graduated from a US medical school. Design Observational study. Setting Medicare, USA. Participants 20% national sample of data for Medicare fee-for-service beneficiaries aged 65 years or older admitted to hospital with a medical condition in 2011-14 and treated by international or US medical graduates who were general internists. The study sample for mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
110
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 31 publications
5
110
3
Order By: Relevance
“…Part B uses fee-for-service payment, and spending varies with the intensity of services delivered, including visits, procedures, and interpretation of tests and images. Based on previous studies, [10][11][12] we defined the responsible physician for a given admission as the physician who billed the largest share of part B costs during that admission. 13 In a sensitivity analysis, we used alternative assignment methods to assess the robustness of our findings to this attribution rule.…”
Section: Patientsmentioning
confidence: 99%
“…Part B uses fee-for-service payment, and spending varies with the intensity of services delivered, including visits, procedures, and interpretation of tests and images. Based on previous studies, [10][11][12] we defined the responsible physician for a given admission as the physician who billed the largest share of part B costs during that admission. 13 In a sensitivity analysis, we used alternative assignment methods to assess the robustness of our findings to this attribution rule.…”
Section: Patientsmentioning
confidence: 99%
“…It is worth mentioning here that a recent report by Tsugawa et al concluded that older Medicare patients treated by IMGs had lower mortality as compared with patients taken care of by AMGs 2. By quoting this paper, we intend to emphasise that IMGs are no less than AMGs in terms of patient care and professional efficiency.…”
mentioning
confidence: 84%
“…In fact, recent studies show that patients whose care was provided by an IMG internist had survival as good as or better than those whose care was provided by US graduate internists. 6,7 Importantly, many IMGs fill much needed physician roles in underserved areas. They provide invaluable care in rural areas of the United States, filling the gaps in health care and physician shortage in those areas.…”
mentioning
confidence: 99%